Optimizing Plant Oil-Derived Lubricants: A Sustainable Alternative to Petroleum-Based Lubricants Using Integer Programming - Sua, Lutfu S.; Balo, Figen (Faculty of Engineering, University of Kragujevac, 2025)
The depletion of fossil-based resources and growing environmental concerns have intensified the search for sustainable alternatives in lubrication. Mineral-based lubricants are becoming increasingly costly and environmentally problematic, necessitating the adoption of plant oil-derived lubricants. These bio-based alternatives offer significant environmental and performance benefits, including biodegradability, non-toxicity, and a reduced carbon footprint, while demonstrating favorable viscosity, lubricity, and thermal stability. However, challenges such as oxidative degradation, production costs, and low-temperature fluidity hinder their widespread adoption. In this study, a comparative evaluation of 13 plant oils was conducted using key physicochemical properties and economic factors. An integer programming model was then employed to optimize the selection process. The integer programming method extends previous research by providing a structured, computationally efficient approach that ensures a single optimal solution rather than a ranked list of potential candidates. The results indicate that rapeseed oil is the most viable option, as it best satisfies critical performance criteria—exhibiting a kinematic viscosity of 45.6 mm²/s at 40°C, a flash point of 513°C, and a cost of only 4.62 per liter—while meeting sustainability benchmarks. The resulting framework not only identifies an optimal bio-based lubricant candidate but also provides practical insights for industrial implementation. Industries can utilize this framework to streamline lubricant selection, ensuring that the chosen formulation meets stringent performance and cost requirements. Policymakers, in turn, can leverage these findings to support the development and adoption of green lubrication technologies. While the results of the optimization model are promising, the proposed lubricant requires further experimental validation under real-world operating conditions to fully assess its long-term performance and durability before widespread industrial application is recommended. © 2025 Published by Faculty of Engineering.
Keywords: Green lubricant; Integer programming; Lubricant; Mathematical optimization; Plant oil; Renewable and sustainable materials